Statistics - Jackson, Sherri L. (Thomson Brooks/Cole, 2005)
STATISTICS: THE EXPLORATION AND ANALYSIS OF DATA, 6th Edition introduces you to the study of statistics and data analysis by using real data and attention-grabbing examples. The authors guide you through an intuition-based learning process that stresses interpretation and communication of statistical information. Simple notation--including the frequent substitution of words for symbols--helps you grasp concepts and cement your comprehension